ФУНКЦИОНАЛЬНАЯ ГРАММАТИКА РАСПРЕДЕЛЯЕТ ПОЛЕ ТАКСИСА (На основе сравнения грамматики азербайджанского и английского языков) - Самедов, Бахруз (Eurasian Journal of Philology Science and Education, 2015)
Carried out by author of the given section the analysis of factors of the Azerbaijan language is directed on studying of interaction of actually time relations between actions from them aspectual signs (duration, frequency rate) and with signs of localization / non-localization and actions in time (closely connected with aspectuality). The analysis subject are also communications of time correlation of actions with semantics of conditionality and relations of characteristic features.